The moderating role of age in the job characteristics-absenteeism relationship: a matter of occupational context? - Bouville, G.; Dello Russo, S.; Truxillo, D. (Journal of Occupational and Organizational Psychology, 2018)
This study addresses the relationship between job characteristics and sickness absenteeism, examining it under two important boundary conditions, employee age, and occupational group. Drawing from psychological theories that explain age-related differences in the workplace, as well as the sociology of occupations, we formulate hypotheses concerning two- and three-way interactions between five key job characteristics (job demands, autonomy, skill variety, supervisor, and colleague support), age, and occupational group, namely blue-collar workers versus clerks. We test our hypotheses on an archival sample of 5,175 employees taken from the French National Survey of Employment Conditions. Hierarchical negative binomial regressions reveal that many of our hypotheses are supported. For example, autonomy and supervisor and colleague support have a differential impact on sickness absenteeism depending on age and the occupational group of employees. We discuss the implications of our findings for both theory and practice.